Postoperative pain experience in post caesarean section mothers in developing countries: A scoping review - Sales, Eurosia Maria; Astuti, Dhesi Ari (Universitas Aisyiyah Yogyakarta, 2025)
Background: The increase in the number of global caesarean sections highlights the importance of understanding the postoperative pain experience as well as the factors that influence patient experience after this procedureObjectives: The aim of this scoping review was to identify the best evidence of pain experience in post-sectio caesarean mothers, evaluate the factors that influence patients' experiences of pain after caesarean sections, and identify barriers to dealing with postoperative pain.Methods: Databases were searched from 2019 to 2023 from various databases, including PubMed, ScienceDirect, and Wiley. As well as using search engines such as Google Scholar and Research Rabbit and selecting them using Mendeley assistance. Critical appraisal and data charting are adopted from the JBI checklist, including cross-sectional, cohort, RCT, and quasi-experimental JBI. Of the 870 articles identified, only nine met the criteria.Results: The results of this review identified three themes, including supporting and inhibiting factors for pain management efforts, the implications of post-sectio cesarean pain, and patient characteristics.Conclusions: Health professionals are advised to implement holistic, evidence-based post-cesarean pain management by combining pharmacological and non-pharmacological methods, supported by improved preoperative education and strict monitoring of analgesic use. An individualized approach and further follow-up studies are essential to optimize maternal recovery and long-term quality of life.